THE TRANSNATIONAL AFFECT ECONOMY: EMOTIONAL CAPITALISM AND THE COMMODIFICATION OF AFFECT IN TAYLOR SWIFT AND INDONESIAN POPULAR MUSIC - Ardana, Stefanus Galang; Christiana, Merry (Pengkajian Amerika, Universitas Gadjah Mada, 2026)
This article examines the transnational flow of emotional capitalism, beginning with Taylor Swift’s industrialization of authentic pain in “All Too Well (10 Minute Version)”. The central problem is understanding how this global model of curated vulnerability is received and reshaped within the Indonesian cultural landscape. This study introduces the “Transnational Affect Economy” as a new analytical framework, synthesizing theories of the Culture Industry, brand culture, and structures of feeling to analyze this process. The analysis of Swift's work reveals a Cinema of Suffering—a deliberate aesthetic strategy that transforms personal heartbreak into a globally marketable emotional product through visual aestheticization and narrative commodification. The findings further demonstrate that this industrial-affective model is not merely replicated but localized by Indonesian musicians Hindia and Nadin Amizah to address the specific structure of feeling known as galau: Hindia packages this sentiment into collective catharsis for urban youth, while Nadin Amizah constructs an introspective, aestheticized refuge—together constituting a